On continuity of operators of metrical projection - Kuznetsov , S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider the metric-projection operators in the space Lp(λ), 1 < p < ∞, where λ ∈ Mb, Mb being the space of bounded Randon measures. The metric-projection operators project a fixed element g ∈ Cb in Lp(λ) onto a closed convex subset K ⸦ Cub, where Cub is the space of bounded continuous functions in the topology of uniform convergence. We obtain statements on the continuity of the metric-projection operators, considered as mappings from Mb into K.